ACCEPTANCE OF PEOPLE WITH DISABILITIES AND THE PLACE OF RESIDENCE. POLISH EXPERIENCES - Kazanowski, Zdzisław; Żyta, Agnieszka (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The acceptance of people with disabilities is multidimensional and is sometimes analyzed concerning various factors. Both external (demographic) factors, e.g. age, gender, place of residence, type of education or occupation, and internal factors (e.g. level of intelligence, self-esteem, sense of coherence) can be taken into consideration. The study presents the results of an analysis of the relationship between the place of residence and the level of acceptance of people with disabilities. The study uses the Disability Acceptance Scale, which consists of 27 statements and is a tool to measure the level of acceptance of people with disabilities in three dimensions: (1) acceptance of support given to people with disabilities; (2) acceptance of inclusion of people with disabilities in the institutions of social life; (3) acceptance of competences of people with disabilities to function in social roles. The study involved 313 people living in south-eastern Poland, including 156 women (49.84%) and 157 men (50.16%) representing three types of residential settings: countryside, small town, and big city. The results of the research revealed that the respondents declared the highest level of acceptance concerning the inclusion of people with disabilities in the institutions of social life (dimension 2), while acceptance of their competence to function in social roles (dimension 3) was at the lowest level. Besides, statistically significant differences were observed between groups separated by place of residence in terms of the intensity of acceptance for the inclusion of people with disabilities in institutions of social life.